ABUNDANCE OF Succinivibrionaceae BACTERIA IN THE FECES OF CALVES FED TANNINS, AMINO ACIDS, AND THEIR COMBINATION - Sitanggang, Fajar Edy Maretno; Fitri, Ainissya; Permana, Idat Galih; Christi, Raden Febrianto (Jurnal Ilmu Ternak Universitas Padjadjaran, 2025)
The purpose of this study was to determine how common Succinivibrionaceae bacteria are in calf feces. Four female calves, with an average age of 6.48 ± 0.51 months, participated in a Latin square trial featuring four dietary treatments: control (C), tannin (T), amino acid (AA), and a tannin-amino acid mixture (TM). Duration of each treatment was 14 days whereby faecal samples were that were harvested on day 14. The treatment trial for 14 days included the collection of faecal samples on day 14 for the extraction of DNA to conduct Next-Generation Sequencing (NGS) analysis. Results showed that the Succinivibrionaceae population grew extensively when treated with T and AA and TM compared with C while AA was most effective. Analysis of bacteria detected five genera and five species. The bacterial genus Ruminobacter dominated in the C (53%) and AA (62%) and TM (58%) treatment groups while Succinivibrio dominated the T treatment group (78%). The species Ruminobacter amylophilus dominated treatments C, AA, and TM but the species Succinivibrio dextrinsolvens dominated treatment T. The results infer that the addition of tannins or amino acids or their combination to the gut environment may help in reducing methane emissions through an alteration in the microbiome composition.